Estimativas da biomassa em carbono do Fitoplâncton Autotrófico da bacia do Espírito Santo por meio do biovolume e sua relação com os valores de clorofila A. - Penha, Juliana da Silva. (2017)
This paper studied the estimation of carbon biomass of autotrophic phytoplankton based on biovolume and verified its relationship with chlorophyll a. Were carried out two oceanographic campaigns, one in winter (July to August 2013) and one in summer (March to April 2014). Were sampled four transects along the Espírito Santo coast, the stations sampled within each transect were organized in eight isobaths the samples were collected at two depths, one subsurface at 1m depth and another at a second depth, which was related or with the Chlorophyll Maximum (PMC) or middle distance between the surface and the bottom (half water), when it was not possible to determine the PMC. The samples were collected both in the continental shelf region and in the slope region. The phytoplankton samples were collected using the Niskin bottle, then preserved with 0.4% formalin and subjected to successive sedimentation processes to count the organisms. The organisms were counted under inverted microscope in random fields and morphometric analysis were carried out to evaluate cell volume, based on the geometric form of algae. To estimate the biomass on carbon (pgC. cell -1 ) were applied different conversion factors, where the biovolume of a certain algae was converted into carbon biomass. The chlorophyll a data of this research belongs to the AMBES Project and were obtained from the Database of Coastal and Oceanic Environments. Was analyzed biomass in carbon of 332 taxa in winter and 304 in summer represented by the Classes Bacillariophyceae, Coccolithophyceae, Coscinodiscophyceae, Cyanophyceae, Dinophyceae, Fragilariophyceae Bacillariophyceae, Coccolithophyceae, Coscinodiscophyceae, Cyanophyceae, Dinophyceae, Fragilariophyceae, among others. The relationship between biomass in carbon and biovolume was significant between periods, between depths and between regions. The Class Cyanophyceae presented low number of species, however, presented one of the highest values in biomass in carbon, represented mainly by the cyanobacterium of the Genus Trichodesmium. In the region of the continental shelf, Coscinodiscophyceae and Cyanophyceae showed in highest values biomass terms the, in the slope region and in the subsurface were Cyanophyceae and Coccolithophyceae classes and second depth were Coscinodiscophyceae and Bacillariophyceae. Was possible to observe spatial and temporal variation of the biomass in carbon, being the highest values recorded in the, subsurface and continental shelf. The relationship between biomass in carbon and chlorophyll a showed to be significant, however low. Was possible to observe significant relationships between these two biomass estimation methods, however, with low values of correlation coefficient in winter (0.36; r2: 0.10), on the continental shelf in winter (0.40, r2 : 0.22) and in the summer slope (0.57; r2: 0.32).The great diversity of techniques for estimating phytoplankton biomass in the literature offers a great variety in the degree of accuracy of the data, and the combinations of biomass estimation techniques may be the best proposal to avoid the limitations of the different methods. Estimates of biomass in carbon by means of the biovolume method have proved to be efficient and extremely important for physiological and ecological studies in marine environments.